THE TEACHING OF ELEMENTARY ACCOUNTING. - Glos, R. E. (The Accounting Review, 1935)
Abstract In this article the author proposes a system for teaching elementary accounting. Because it might be contended that this paper is attempting to make a virtue out of necessity or rationalizing that which had to be, according to the author, the system of teaching accounting at Miami University, Ohio was inaugurated before restrictive legislative appropriations might have forced the same system on accountants. Furthermore, because of the latter factor, it may be that what accountants are doing is not now as unique as it might have been some years before. According to the author, laboring under a delusion in believing there is or ever was anything unique in methods. All students take the same course regardless of whether they are accounting majors, business students interested in other majors, or students in other divisions of the University taking the course for various reasons.